2023
DOI: 10.1007/s10518-023-01676-0
|View full text |Cite
|
Sign up to set email alerts
|

Residential building stock in Serbia: classification and vulnerability for seismic risk studies

Abstract: Regional seismic risk assessment is necessary for designing effective seismic risk mitigation measures. In general, such risk assessment studies consist of three components: hazard, vulnerability, and exposure modelling. This paper lays the foundations for regional seismic risk assessment of the residential building stock in Serbia and addresses each of the three seismic risk assessment components, either by reviewing the existing or proposing novel models. First, a review of seismic hazard models and seismic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The pioneering investigation by Blagojević et al [19] yielded illuminating insights, particularly concerning the resilience demonstrated by modern confined masonry structures characterized by meticulously constructed RC confining elements, notably observed during the seismic event of 2010 in Kraljevo, Serbia. However, a stark contrast emerged with structures exhibiting inadequately reinforced confining elements and walls featuring horizontally aligned perforations in modular clay blocks, which succumbed to damage.…”
Section: Analysis Of Confined Masonry Structures In Ex-yugoslaviamentioning
confidence: 99%
See 1 more Smart Citation
“…The pioneering investigation by Blagojević et al [19] yielded illuminating insights, particularly concerning the resilience demonstrated by modern confined masonry structures characterized by meticulously constructed RC confining elements, notably observed during the seismic event of 2010 in Kraljevo, Serbia. However, a stark contrast emerged with structures exhibiting inadequately reinforced confining elements and walls featuring horizontally aligned perforations in modular clay blocks, which succumbed to damage.…”
Section: Analysis Of Confined Masonry Structures In Ex-yugoslaviamentioning
confidence: 99%
“…The variable thickness of these walls, ranging from 19 to 38 cm, was contingent upon the structure's elevation and the specific masonry unit employed. Conversely, multi-family residential buildings typically featured exterior wall thicknesses ranging from 38 to 51 cm and interior wall thicknesses spanning 25 to 30 cm, a testament to the nuanced structural considerations entailed in their design and construction [19].…”
Section: Analysis Of Confined Masonry Structures In Ex-yugoslaviamentioning
confidence: 99%
“…On 3 November 2010, a magnitude (ML)-5.4 earthquake affected the city of Kraljevo, Serbia, and the neighboring villages. The earthquake caused two fatalities and affected more CM construction has been practiced in the Balkan region, particularly within the territory of Yugoslavia [2], since 1964, when the first seismic design code, PTP-12 [3,4], was published. A subsequent version of the code, PTN-S, was issued in 1981 [5], and it was enforced within the territory of Yugoslavia until the 21st century, although the breakdown of the country occurred in 1991.…”
Section: Introductionmentioning
confidence: 99%